Niveles sanguíneos de ampicilina en pollos de engorde (1990)
Ampicillin has shown be usseful in the treatment of sicknees infections of respiratory tract of broilers. Dosage administration is based in terapeutical clinical efficacy, but there is know very little about the serum concentrations, and in another corporeal tissues. The aim of this work was blood concentrations specifity of the ampicillin in 90 broilers during 49 days when by oral means was given to the dosage of 10, 25 and 40 mg/kg of living weight. This chickens were weight homogenizazed and random entirely chosen with factorial arrangements of 4 x 5 with 5 repetitions and 1 chicken by each repetitions; 15 of this chickens were used as a control, and therefore none of this received antibiotical treatment. Blood samples were obtained after 1/2, 1, 2, 4 and 8 hours medicamental postadministration. Significatives differences were observed by dosage effect of ampicillin studied about the himself concentration in the blood (P 'K 0.01). The time has a significative meaning about the concentration of ampicillin activity in blood (P<0.05). Time ampicillin interactions was no significative difference. The in blood serum averages were of 0.471, 0.841 and 1.459 mcg/ml for dosages of 10, 25 and 40 mg/kg of living weight. Dosage of 40 mg/kg was found in concentrations of serum under 5 mcgfml at different times, which suggested to give a higher dosage than the normally used, to get in concordance with the minimal inhibitory concentration (MIC) and to obtain higher concentrations in vitro, determined for the main germs agains which ampicillin is active.